Analisis Dampak Persepsi Ancaman Drone Terhadap Pembuatan Kebijakan Pertahanan Dan Proses Alokasi Sumber Daya - Aris Sarjito; Nora Lelyana (Jurnal of Management and Social Sciences, 2023)
Drones have significantly impacted modern warfare, necessitating a comprehensive understanding of the factors influencing drone threat perceptions and their impact on defense policymaking. This study examines the influence of drone threat perceptions on defense policymakers' decision-making and resource allocation, focusing on key factors influencing perception formation. This study uses qualitative research methodology to analyze secondary data from academic research, policy reports, and expert analysis to identify recurring themes and patterns in defense policymakers' perceptions of drone threats. The research findings highlight that varying drone threat perceptions significantly impact defense policymakers' decision-making processes. Key factors influencing the formation of drone threat perceptions include geographical proximity, technological advancements, and past experiences. These threat perceptions shape defense resource prioritization, with a greater emphasis on acquiring counter-drone technologies and air defense systems. The implications of defense resource allocation under prevailing drone threat perceptions are significant. Allocating resources effectively to address drone threats necessitates a comprehensive understanding of threat perceptions and their impact on defense priorities. Overall, this research demonstrates that drone threat perceptions substantially influence defense policymaking and resource allocation. Understanding the key factors shaping these perceptions is crucial for policymakers to better respond to the evolving drone threat.